2014
DOI: 10.12973/jesr.2014.42.10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of argumentation on metacognition and logical thinking abilities in science–technology teacher candidate education and opinions about argumentation

Abstract: Bu araştırmada, hizmet öncesi öğretmen eğitiminde argümantasyonun farklı şekillerde işleniş modelinin fen-teknoloji öğretmen adaylarının biliş üstü ve mantıksal düşünme becerilerine etkisini inceleyerek, argümantasyonla ilgili görüşlerin belirlenmesi amaçlanmıştır. Araştırmanın çalışma grubunu 2010-2011 ve 2011-2012 öğretim yılı Hacettepe Üniversitesi Fen Bilgisi Öğretmenliğinde öğrenim gören 135 kişilik grup oluşturmaktadır.Araştırma yöntemi olarak deneysel desenlerden ön test-son test kontrol gruplu desen, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 6 publications
1
5
0
1
Order By: Relevance
“…In this context, although there are different learning teaching methods, techniques and activities in the literature, when the studies using scientific scenarios are examined, it is seen that some of them have an effect on the development of logical thinking skills, and some of them have no effect on the development of logical thinking skills. Aydın and Kaptan (2014) examined the development of logical thinking skills of groups in which argumentation-based education was applied using scenarios. The authors found that by presenting the scenarios, the group in which the argumentation was made developed the logical thinking skills significantly.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, although there are different learning teaching methods, techniques and activities in the literature, when the studies using scientific scenarios are examined, it is seen that some of them have an effect on the development of logical thinking skills, and some of them have no effect on the development of logical thinking skills. Aydın and Kaptan (2014) examined the development of logical thinking skills of groups in which argumentation-based education was applied using scenarios. The authors found that by presenting the scenarios, the group in which the argumentation was made developed the logical thinking skills significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Argumentation-based learning is one of the educational environments where students often find the opportunity to use their 21 st -century skills, such as the ability to use various strategies in the process of solving problem situations that reflect real-world problems, to enter the scientific discussion process by evaluating the claims with data and grounds, to think critically, to make judgments, to use scientific thinking skills, and to make scientific decisions (Eyceyurt Türk & Kılıç, 2020). In relevant literature, argumentation-based learning have shown to provide positive changes in many cognitive and affective variables in students: increase in students' social understanding and environmental awareness (Fettahoğlu, 2016), development of argument skills (Topçu & Atabey, 2017) and higher-order thinking skills (Yıldırır & Nakiboğlu, 2014), increase in science achievement (Öğreten & Uluçınar, 2014) and conceptual understanding (Acar, Tola, Karaçam & Bilgin, 2016;Eyceyurt Türk & Güngör Seyhan, 2022;Okur & Güngör Seyhan, 2021;Tezel & Yaman, 2017), positive change in metacognitive strategies (Aydın & Kaptan, 2014;Ulu & Bayram, 2014), the establishment of science culture in students, activating scientific reasoning and logic skills, and gaining scientific literacy (Jiménez-Aleixandre & Erduran, 2008).…”
Section: Argumentation-based Learningmentioning
confidence: 99%
“…Argümantasyon tabanlı fen eğitiminin amacı yalnızca fen kavramlarına hâkim olmak değil, bilimsel bir açıklama diline sahip olabilmektir (Kuhn, 2009). Fen okuryazarlığına katkı sağlama, kavramsal anlama, araştırma, eleştirel düşünme ve akıl yürütme becerilerini geliştirme, argümantasyon tabanlı öğrenmenin temel amaçları olarak kabul edilmektedir (Aydın ve Kaptan, 2014).…”
Section: Türk Fen öğRetim Programlarını Etkileyen Disiplinlerarası Yönelimlerunclassified